Technical, tactical, and time-motion match profiles of the forwards, midfielders, and defenders of a men`s football Serie A team - Perrotta, R.; Ungureanu, A. N.; Cherubini, D.; Brustio, P.R.; Lupo, C. (Sports, 2025)
The present study aimed to verify the (1) differences between players` roles in relation to technical and tactical and time-motion indicators, and the (2) relationships between individual time-motion and technical and tactical indicators for each role in a men`s Italian football Serie A team. A total of 227 performances were analyzed (28 players: 8 forwards, FWs; 11 midfielders, MDs; 9 defenders, DFs). Technical and tactical indicators, such as ball possession (played balls, successful passes, successful playing patterns, lost balls, ball possession time), offensive play (total and successful dribbles, crosses, assists), and shooting (total shots, shots on target) were obtained by means of Panini Digital (DigitalSoccer Project S.r.l). In addition, a time-motion analysis included the total distance, distances covered at intensities of 16.0-19.8 km/h, 19.8-25.2 km/h, and over 25.2 km/h, the average recovery time between metabolic power peaks, and burst occurrence, the latter of which was performed by means of a 18 Hz GPS device (GPexe Pro2 system tool) worn by the players. Results showed role-specific differences: MDs covered more distance, while DFs had better ball possession. MDs and DFs had more successful playing patterns, and MDs and FWs performed more dribbles and shots. Strong correlations (p < 0.01, rho > 0.8) were found between bursts and assists for FWs, high-intensity running and ball possession for MDs, and distance, dribbling, and shots for DFs. These findings highlight the importance of individual and tailored training programs to optimize role-specific performance demands.